Influence of Anatomical Parameters on the Dimensions of the Subantral Space and Sinus Mucosa Thickening after Sinus Floor Elevation. A Retrospective Cone Beam Computed Tomography Study - Yuki Omori; Yasushi Nakajima; Hideki Imai; Daichi Yonezawa; Mauro Ferri; Karol Alí Apaza Alccayhuaman; Daniele Botticelli (MDPI AG, 2021)
Background: Various anatomical parameters might influence the surgical approach for maxillary sinus floor elevation. The objective of the present study was to retrospectively evaluate the influence of anatomical parameters on the dimensions of the subantral space and of the sinus mucosa thickening after sinus floor elevation. Material and Methods: Seventy-eight maxillary sinuses in sixty-five patients were evaluated on cone beam computed tomographies taken before surgery and after one week (t1w) and nine months (t9m). Several parameters such as the distance XF between an axis parallel to the base of the nose (X-axes) and the sinus floor (F) were correlated with the height gain (IF) at t1w and t9m and the post-surgical edema. Results: A weak significant positive correlation was observed between height gain vs. sinus height of interest (XF), the balcony, and the sinus floor angle. The post-surgical edema was influenced by the initial mucosa thickness and the xenograft used. Conclusions: Various parameters might affect height gain and sinus mucosa thickening after sinus floor elevation. The height of interest, the balcony, and the sinus floor angle showed significant correlations with height gain. The initial thickness of the mucosa and the biomaterial used influenced the post-surgical edema.